Nanophytosome delivery model based on a combination of bay leaf (syzygium polyanthum) and binahong (anredera cordifolia) extracts in gel formulation as a therapy for diabetic ulcers - Arip Saifurrohman; Garnadi Jafar; Entis Sutrisno (Science Midwifery, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia and associated with various complications, including diabetic foot ulcer (DFU), which may lead to infection, gangrene, amputation, and even death. Natural-based topical therapies have potential to support DFU healing; however, the limited solubility and permeability of active compounds, particularly polar phytochemicals, often reduce their therapeutic effectiveness. Nanophytosomes, a phospholipid–phytoconstituent complex system, are considered capable of enhancing the stability and penetration of herbal compounds. This study aimed to design and develop nanophytosomes containing a combination of bay leaf extract (Syzygium polyanthum) and binahong leaf extract (Anredera cordifolia), characterize the system, incorporate it into a gel formulation, and evaluate its wound-healing activity in a diabetic wound model. The study involved preparation of nanophytosomes from the combined extracts followed by characterization of particle size, polydispersity index (PDI), zeta potential, entrapment efficiency, and particle morphology. The nanophytosome system was then formulated into a gel and evaluated for physical quality parameters including pH, viscosity, spreadability, and stability. Wound-healing activity was assessed using a diabetic wound model in experimental animals by observing wound closure and histological parameters. The expected results include the formation of nanophytosomes with favorable physicochemical characteristics, a stable gel formulation, and improved diabetic wound healing compared with the control group. It is anticipated that the nanophytosome gel combining S. polyanthum and A. cordifolia extracts may serve as a promising innovative topical therapy for DFU.